Hack proofing your Web applications - Traxler, Julie (Rockland, Mass. : Syngress Pub., 2001)
From the authors of the bestselling Hack Proofing Your Network! OPEC, Amazon, Yahoo! and E-bay: If these large, well-established and security-conscious web sites have problems, how can anyone be safe? How can any programmer expect to develop web applications that are secure? Hack Proofing Your Web Applications is the only book specifically written for application developers and webmasters who write programs that are used on web sites. It covers Java applications, XML, ColdFusion, and other database applications. Most hacking books focus on catching the hackers once they've entered the site; this one shows programmers how to design tight code that will deter hackers from the word go. Comes with up-to-the-minute web based support and a CD-ROM containing source codes and sample testing programs Unique approach: Unlike most hacking books this one is written for the application developer to help them build less vulnerable programs.
Includes index.
"The only way to stop a hacker is to think like one."
Keywords: Computer security; Internet -- Security measures; Computer networks -- Security measures; Web sites -- Design; Electronic books